2015
DOI: 10.1590/1983-40632015v4534593
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of inoculant with Azospirillum brasilense on the growth and yield of second-harvest maize1

Abstract: The misuse of fertilizers has become a growing concern in terms of agricultural and environmental sustainability. One alternative to reduce the impact of chemical fertilizers is the use of inoculants containing nitrogen-fixing and plant growth promoting bacteria. This study aimed at evaluating the effects of an inoculant with Azospirillum brasilense on the growth and yield of secondharvest maize. The experimental design was randomized blocks with three replications, in a 3 × 5 factorial scheme. The treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 13 publications
4
27
0
9
Order By: Relevance
“…Except when using the commercial dose of the inoculant (T4), once more all the treatments in which the inoculant was combined with N fertilizer had higher or equal CC values than the treatment in which the full recommendation of N fertilizer was employed (T2). Such as in the present work, Quadros et al (2014), Costa et al (2015) and Araújo et al (2015) also reported increasing in CC after seed or foliar inoculation in maize.…”
Section: Chlorophyll Content (Cc)supporting
confidence: 87%
See 1 more Smart Citation
“…Except when using the commercial dose of the inoculant (T4), once more all the treatments in which the inoculant was combined with N fertilizer had higher or equal CC values than the treatment in which the full recommendation of N fertilizer was employed (T2). Such as in the present work, Quadros et al (2014), Costa et al (2015) and Araújo et al (2015) also reported increasing in CC after seed or foliar inoculation in maize.…”
Section: Chlorophyll Content (Cc)supporting
confidence: 87%
“…In this regard, while in Biari et al (2008), Braccini et al (2012), Costa et al (2015) and Morais et al (2016) found an increase in seed weigh of maize after plant inoculation combined to N fertilizer rates, on the other hand, in Novakowiski et al (2011) there was no significant interaction between N levels and inoculation for TSW. However, while the later authors used the bacteria strain Sp245, Hungria et al (2010) pointed out that only the strains AbV4, AbV5, AbV6 and AbV7 are the most effective for maize.…”
Section: Thousand Seed Weight (Tsw)mentioning
confidence: 90%
“…Ramos et al (2010) mentioned that the interaction of A. lipoferum BR 11084 strain on corn showed a significant development as far as nitrogen fertilization. Costa (2015) also observed the positive effect of A. brasiliense Ab-V5 and Ab-V6 strains and nitrogen fertilization association at vegetative growth stage of maize and at dry mass of stalk and leaves. De Oliveira et al (2015) reported that Pseudomonas supported corn plants in their growth and increased the length and diameter of ears.…”
Section: Figure 1 -Effect Of Bacteria Isolates Inoculation At Plant Hmentioning
confidence: 59%
“…However, the high cost of nitrogen fertilizers and the growing concern about the development of a more sustainable and less polluting agriculture, lead to the search for alternatives to reduce the environmental impact of chemical fertilizers (Costa, Quirino, Naves, Santos, & Rocha, 2015), without causing losses in productivity.…”
Section: Introductionmentioning
confidence: 99%
“…And, on a larger scale, for the production of phytohormones, responsible for the increase of the surface area of the roots of grasses and, consequently, larger area explored in the soil with increase in the absorption of minerals, including the N, and water, resulting in a more productive and resistant plant (Moreira, Silva, Nóbrega, & Carvalho, 2010;Hungria, Campo, Souza & Pedrosa, 2010;Costa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%